2021
DOI: 10.3390/separations8110223
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Rhizobacteria Modulate the Concentration of Bioactive Compounds in Tomato Fruits

Abstract: Background: The application of microorganisms as bioestimulants in order to increase the yield and/or quality of agricultural products is becoming a widely used practice in many countries. In this work, five plant growth-promoting rhizobacteria (PGPR), isolated from cultivated rice paddy soils, were selected for their plant growth-promoting capacities (e.g., auxin synthesis, chitinase activity, phosphate solubilisation and siderophores production). Two different tomato cultivars were inoculated, Tres Cantos an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The tomato carotene concentration was similar to previous reports by de la Osa et al. (2021) and Ruiz‐Cisneros et al. (2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The tomato carotene concentration was similar to previous reports by de la Osa et al. (2021) and Ruiz‐Cisneros et al. (2022).…”
Section: Discussionsupporting
confidence: 91%
“…De la Osa et al. (2021) evaluated Pseudomonas strains for their role in plant development and lycopene content and reported that lycopene content increased by 2.33 and 16.0 mg/100 g FW compared to the NPK control. The antioxidant activity of tomato fruit extracts was measured using DPPH.…”
Section: Discussionmentioning
confidence: 99%
“…According to Suriani et al (2021), using B. agri at 1-2% can enhance the phenolic content, flavonoids, antioxidant activity, and chlorophyll content in Piper caninum herbal plants. Applying rhizobacteria derived from rice roots on toman cantos plants has enhanced the bioactive lycopene content and antioxidant activity (de la Osa et al, 2021). The combination of PGPR and salicylic acid can improve the levels of secondary metabolites, precisely phenolic compounds and monoterpenes, in Mentha x piperita plants (Del Rosario Cappellari et al, 2020;de la Osa et al, 2021).…”
Section: Analysis Of Phytochemicals Chlorophyll Antioxidants and Heav...mentioning
confidence: 99%
“…Applying rhizobacteria derived from rice roots on toman cantos plants has enhanced the bioactive lycopene content and antioxidant activity (de la Osa et al, 2021). The combination of PGPR and salicylic acid can improve the levels of secondary metabolites, precisely phenolic compounds and monoterpenes, in Mentha x piperita plants (Del Rosario Cappellari et al, 2020;de la Osa et al, 2021). Inoculating Mucilaginibacter sp.…”
Section: Analysis Of Phytochemicals Chlorophyll Antioxidants and Heav...mentioning
confidence: 99%
See 1 more Smart Citation